EDUCATIONAL PLACEMENT OF SCHOOL-AGED CHILDREN WITH AUTISM IN CHINA (Proceedings of International Conference on Special Education, 2015)
Autism is a neurodevelopmental disorder, characterized by difficulties in social interaction, verbal and non-verbal communication and restricted and repetitive behavior. With increasing number of school-age children with autism in China, regular schools refuse to accept them due to the lack of professional services and resources. This caused some children with autism drop out of school, some even commit suicide. As a result, where to place them and how to provide appropriate education becomes one of the focus points of special education academe in China. Chinese government has put forward Special Education Promotion Plan (2014-2016) in 2014, which clearly encourages to establish specific special schools (departments) for children and adolescents with autism. This paper reviews the development of educational placement for children with autism internationally, then draws a conclusion that developed countries are trying to provide diverse educational placement options (including special schools, regular schools, special classrooms in regular schools, as well as providing home services) to meet the complex educational needs of children with autism. This paper also discusses the feasibility to establish special schools for children with autism and explicitly point out that as one of the diverse educational placement, the purpose of special schools of children with autism is to satisfy the diverse educational needs of severe and moderate children with autism with low functioning. In the end, this study provides suggestions in improving diverse educational placement for children with autism in China